2020
DOI: 10.1053/j.gastro.2020.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis Is Not Required for Endoscopic Ultrasonography-Guided Fine-Needle Aspiration of Pancreatic Cystic Lesions, Based on a Randomized Trial

Abstract: *No differences in the incidence of infection or other events 500 mg bid (3 days) 200 mg iv (1 dose) • Infection after EUS-FNA is low • The use of antibiotic prophylaxis is conflicting Antibiotic Prophylaxis is Not Needed for EUS-guided FNA of Pancreatic Cystic Lesions: a Clinical Trial Results: • Non-inferiority multicenter clinical trial 226 iv (1 dose) bid (3 days) 112 ciprofloxacin 0 (0%) 2 (1.78%) 6 (5.4%) Infection Fever Other events 114 placebo 1 (0.87%) 2 (1.76%) 8 (7%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 20 publications
3
40
0
Order By: Relevance
“…These were effective during the study period, and recommended antibiotic prophylaxis before and 3 to 5 days after EUS-FNA, although the conflicting evidence. Recent evidence from a randomized trial published in 2020, showed that antibiotic prophylaxis might not be needed at all before EUS-FNA of pancreatic cysts [29].…”
Section: Discussionmentioning
confidence: 99%
“…These were effective during the study period, and recommended antibiotic prophylaxis before and 3 to 5 days after EUS-FNA, although the conflicting evidence. Recent evidence from a randomized trial published in 2020, showed that antibiotic prophylaxis might not be needed at all before EUS-FNA of pancreatic cysts [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recent randomized controlled trial suggests that there is no role of antibiotic prophylaxis before pancreatic cyst aspiration. 28 In the absence of a mass like lesion (mural nodule) and in presence of multiple cysts, the largest cyst alone is aspirated. If a different cyst needs to be aspirated, a new needle should be taken.…”
Section: Selection Of Needlementioning
confidence: 99%
“…Puncture of cystic lesions is usually followed by antibiotic administration, acting as prophylaxis for infectious complications. Although this policy has been integrated into everyday worldwide clinical practice, its efficacy remains questionable, given the fact that the actual risk for infection remains very low (less than 1%) [ 26 ]. The latest ASGE guidelines suggest the use of prophylactic antibiotics only in cases of EUS-FNA of mediastinal and pancreatic cystic lesions; however, this was merely a weak recommendation, underlining the fact that data from prospective, randomized studies were lacking [ 27 ].…”
Section: Qis In the Pre-procedures Phasementioning
confidence: 99%
“…The latest ASGE guidelines suggest the use of prophylactic antibiotics only in cases of EUS-FNA of mediastinal and pancreatic cystic lesions; however, this was merely a weak recommendation, underlining the fact that data from prospective, randomized studies were lacking [ 27 ]. Indeed, the very first randomized trial evaluating the effect of antibiotic prophylaxis on the incidence of pancreatic cyst infection after EUS-FNA was only published very recently [ 26 ]. In this multicenter, randomized, non-inferiority trial conducted in Spain, prophylaxis with ciprofloxacin was compared against placebo administration in patients undergoing EUS-FNA for pancreatic cystic lesions.…”
Section: Qis In the Pre-procedures Phasementioning
confidence: 99%